1990
DOI: 10.1002/jobm.3620300202
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylmuramic acid inhibits spore germination and germination enzymes

Abstract: This report describes the inhibition of spore germination by N-acetylmuramic acid. At concentrations of 20 mM and higher, the rate of germination of the treated spores was ten-fold lower than that of the control spores. The inhibitor also depressed the activity of two germination-related enzymes; a coat-associated hexosaminidase and a core enzyme. These findings suggests that N-acetylmuramic acid affects spore germination by inhibition of the corticolytic enzymes. The results are discussed with respect to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Protease inhibitors and sulphydryl reagents significantly inhibit nutrient germination of spores in a number of Bacillus species [30,56,[60][61][62][63][64][65][66]. It has been suggested that cadmium acetate, N-ethylmaleimide and HgCl 2 target essential sulphydryl groups of proteins involved in the early steps of spore germination [65].…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%
“…Protease inhibitors and sulphydryl reagents significantly inhibit nutrient germination of spores in a number of Bacillus species [30,56,[60][61][62][63][64][65][66]. It has been suggested that cadmium acetate, N-ethylmaleimide and HgCl 2 target essential sulphydryl groups of proteins involved in the early steps of spore germination [65].…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%